Expansion within the CYP71D subfamily drives the heterocyclization of tanshinones synthesis in Salvia miltiorrhiza - Ying Ma (Nature Portfolio, 2021)
Salvia miltiorrhiza is a medicinal plant that can produce the bioactive tanshinones. Here, the authors report the improved genome assembly and reveal the possible roles of three CYP71Ds in catalyzing the reactions leading to the formation of the characteristic furan D-ring of transhinones.